2022
DOI: 10.1155/2022/6010952
|View full text |Cite
|
Sign up to set email alerts
|

Using Network Pharmacology and Animal Experiment to Investigate the Therapeutic Mechanisms of Polydatin against Vincristine-Induced Neuropathic Pain

Abstract: Background. Polydatin (PD) is the primary active compound in Polygonum cuspidatum Sieb and has been demonstrated to exert anti-inflammatory and neuroprotective activities. In the present study, we aimed to explore the therapeutic mechanisms of PD against chemotherapy-induced neuropathic pain. Methods. The putative targets of PD were obtained from the CTD and SwissTargetPrediction databases. Neuropathic pain- and VIN-related targets were collected from the CTD and GeneCards databases. Subsequently, the intersec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Additionally, in a neuropathic pain model, miR-7a has been observed to be the most greatly decreased miRNA in the dorsal root ganglion, and upregulation of miR-7a resulted in recovery from neuropathic pain [37]. It has been experimentally shown that miR-137-3p regulates CDK6 [38] and KIT [39], while miR-378a-3p regulates specific pain-related genes including casp9 [40][41][42], IGF1R, MAPKAPK2, ODC1 [43], PPARA [44,45], and TP53 [46][47][48][49]. The miRNAs identified in this study are potential therapeutic targets and treatments for neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a neuropathic pain model, miR-7a has been observed to be the most greatly decreased miRNA in the dorsal root ganglion, and upregulation of miR-7a resulted in recovery from neuropathic pain [37]. It has been experimentally shown that miR-137-3p regulates CDK6 [38] and KIT [39], while miR-378a-3p regulates specific pain-related genes including casp9 [40][41][42], IGF1R, MAPKAPK2, ODC1 [43], PPARA [44,45], and TP53 [46][47][48][49]. The miRNAs identified in this study are potential therapeutic targets and treatments for neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Polydatin (PD) serves as the primary active ingredient of Polygonum cuspidatum Sie , renowned for its anti-inflammatory and neuroprotective properties. In the context of neuropathic pain induced by vincristine (VIN) in rats, PD was observed to curtail the levels of TP53, IL-6, and MAPK1 ( Xi et al, 2022 ). Further investigations employed an in vivo model involving adenovirus-induced GO mice expressing the TSHR A-subunit (Ad-TSHR289), as well as an in vitro study using hydrogen peroxide (H 2 O 2 )-induced oxidative stress on OFs.…”
Section: Tcm and Other Treatmentsmentioning
confidence: 99%
“…Polygonum cuspidatum SiebRelieved orbital muscle adipose tissue expansion and reduced lipid droplet accumulation through NRF2-mediated oxidative stress response and downregulation ofIL-6 Li et al (2020c),Xi et al (2022) DiosgeninTrigonella foenum-graecum L Reduced thyrocyte proliferation, thyroid size, and T4 levels in GD mice.Inhibited the PI3K-AKT and Rap1-MEK signaling pathways and promoted thyroid cell apoptosisHe et al (2012),Cai et al (2014), Xin et al (2021) Resveratrol Reynoutria japonica Houtt Reduced proinflammatory cytokine IL-6, IL-8, and TNF-α in HaCat cells. Reduced ROS production, suppressed adipogenesis, and reduced the number of adipocytes in GO orbital fibroblasts in vitro by increasing the expression of the p-JNK and transcriptional regulators p-ERK Ravagnan et al (2013), Kim et al (2015) Icariin Epimedium Inhibited the differentiation of preadipocytes into mature adipocytes, lipid droplet accumulation, and orbital muscle adipose tissue expansion by inhibiting AMPK/mTOR-mediated autophagy in GO mouse models Li et al (2017), Wang et al (2020) Celastrol Celastrus orbiculatus Thunb Reduced the IL-1β-induced expression of IL-8, IL-6, ICAM-1, and COX-2 in OFs from patients with GO Li et al (2016) Gypenosides Gynostemma pentaphyllum Downregulated IL-8, L-6, TNF-α, CCL, HAS2, COL1A2, FN1, and α-SMA in OFs induced by IL-1β and TGF-β through reducing the activation of TLR-4/NF-κB signaling and TGF-β1/SMAD2/ SMAD4 signaling in GO OFs Wang et al (2017), Li et al (2019), Li et al (2020b), Ma et al (2022) Astragaloside IV Astragalus memeranaceus Downregulated inflammatory cytokines, and attenuated collagen deposition, fat accumulation, and macrophage infiltration of GO OFs Li et al (2018) Ursolic acid, rutin, and Prunella vulgaris polysaccharides Prunella vulgaris Ursolic acid and rutin promoted apoptosis and regulated immune systems in cell and animal models Zhang et al (2020b).…”
mentioning
confidence: 99%